Examining the Role of Intention and Perceived Behavioral Control on Purchase of Ethical Products in Rwanda - Denyse, Mukandoli; Bhagat, Deepak (Indian Journal of Marketing, 2018)
Though there is evidence that more and more consumers have endorsed and are motivated by the values of ethical consumerism, literature has reported that stated ethical intentions seldom translate into actual ethical buying behaviour. After the large scale devastation of humans and the environment during the genocide perpetrated against Tutsi in 1994, Rwanda, with support from United Nations Environment Programme (UNEP) and different business houses, has now decided to brand itself as one of the greenest countries in the world by leveraging a ’green economy’ approach to economic development. The attainment of the above objective will depend on ethical consumption behaviour of Generation Y as the mean age in Rwanda is only 21.9 years. In the above context, based on Ajzen’s theory of planned behaviour (1991), with the responses from 400 Generation Y consumers of Rwanda, the study attempted to examine the role of intention and perceived behavioral control on purchase of ethical products. The respondents showed strong intention in favour of environmental ethical products as compared to animal and human ethical products. The purchase behavior, as the targeted behavioral outcome, was better for animal ethical products. Women were ahead of men in their purchasing behavior towards ethical products. The relationship between purchase intentions and perceived behavioral control related to purchase behavior was positive and significant. It is recommended to highlight significance of animal welfare, environment protection, and human rights and provide tax exemptions, subsidies, and better investment opportunities to business houses promoting ethical products and practices among consumers.